Natixx090
Rozwiązane

1. Zapisz w najprostszej postaci:

a) y ∙ x ∙ (-5) ∙ 7x ∙(-15 ) ∙ 2y =

b) (−18) ∙(−7)−3=

c) -(3x + y - 5) – (2x – 3y + 4) – (x – 2y - 2) =

2. Zredukuj wyrazy podobne, a następnie oblicz wartości liczbowe wyrażeń:

a) 4x – (x2 – 5) dla x = -2

b) 2x2 – y(x + 3) dla x = -4, y = 3

c) 9a + 8 – 5a + 3 + 4a – 8 dla a = -3

d) 6x + 5y + 9 – 7x + 3y - 2 dla x = 4, y = -0,2

e) b2 + b – 8 - 3b2 – 3n – 9 – n + 17 dla n = −12 b = -2

f) (3a2 + 1) – 3(a2 – a) + 14 dla a = 2,3

g) (x2 + 2xy – 1) - (x2 – 4xy + 5) dla x = 16 i y = 3